Appraisal of improved salt selectivity in polyvinylidene difluoride membranes for water desalination: Methods, mechanism, and prospects - Ratnasari, Anisa; Soedjono, Eddy Setiadi; Tangahu, Bieby Voijant; Yuniarto, Adhi; Zainiyah, Isti Faizati; Hadibarata, Tony; Sharma, Sunny; Thakur, Samrendra Singh (Monatshefte für Chemie, 2025)
The advancement of robust technology in water desalination presents several approaches and challenges. Polymer membrane separation has been acknowledged as a promising technique for effectively addressing water desalination. Polyvinylidene difluoride (PVDF), as one of the polymer membranes, has seen increasingly rapid advances in the field of separation process due to its preferable properties, such as reusability properties, mechanical strength, hydrophilicity/hydrophobicity properties, thermal properties, antifouling properties, and chemical resistance. Several enhancement approaches have been employed to modify its surface to gain better properties, such as free radical polymerization, photo-induced polymerization, and plasma-induced polymerization. The modification of the PVDF membrane can impact its structure, pore size, pore size distribution, and porosity. As a consequence, the mass transfer of a certain amount of salt and salt ions is interfered with the membrane surface. This review aims to evaluate the advancement of techniques related to the salt selectivity enhancement in the case of the PVDF membranes used for desalination of water, explain the reasons for these advances, and suggest the perspectives for this direction of research. As such, this review gives an elaborate assessment of the processes incorporated in the alteration of PVDF membranes such that enhanced separation and rejection of salts is done while allowing for the free flow of the solvent water. It also examines the molecular as well as structural factors that influence the factors with understanding how the performance of membranes could be influenced by those modifications. In contrast to the existing literature on the subject, this review focuses on how membrane structure properties relate with membrane modification which has not been sufficiently addressed in research. In addition, this review examines the potential of PVDF membranes in desalination applications in view of the recent developments in the membranes that would enable the membranes to be used in industrial processes. In doing so, this review also seeks to address the current challenges related to the theory and practice of desalination technologies and considers the new avenues of their development in light of the most promising current research findings.